2005
DOI: 10.4315/0362-028x-68.7.1472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Inhibition of Listeria spp. by Vanillin and Vanillic Acid

Abstract: The antimicrobial effects of vanillin and vanillic acid were verified against several species and strains of Listeria monocytogenes, Listeria innocua, Listeria grayi, and Listeria seeligeri in a laboratory medium adjusted to pH values ranging from 5.0 to 8.0. Medium pH had little influence on the MIC of vanillin as determined by a broth dilution assay, and growth of all test strains was inhibited by concentrations ranging from 23 to 33 mM. In contrast, none of the strains were inhibited by 100 mM vanillic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 24 publications
2
56
0
1
Order By: Relevance
“…The wealth of stem and gall extracts in phenolic acids (in particular vanillic acid) and flavonoids (especially quercetin) award to these organs important antioxidant and antimicrobial capacities. These results are corroborated by Delaquis et al (2005) proved that vanillic acid possess many physiological and pharmacological functions (Varma et al 1993;Singh et al 2006). On the other hand, Yamamoto et al (1999); Katsube et al (2006), and Boots et al (2008) demonstrated the role of quercetin to scavenge free radicals and reactive species, thereby reducing oxidative stress and their associated damages.…”
Section: Phenolic Composition Of Limoniastrum Monopetalum Organssupporting
confidence: 93%
“…The wealth of stem and gall extracts in phenolic acids (in particular vanillic acid) and flavonoids (especially quercetin) award to these organs important antioxidant and antimicrobial capacities. These results are corroborated by Delaquis et al (2005) proved that vanillic acid possess many physiological and pharmacological functions (Varma et al 1993;Singh et al 2006). On the other hand, Yamamoto et al (1999); Katsube et al (2006), and Boots et al (2008) demonstrated the role of quercetin to scavenge free radicals and reactive species, thereby reducing oxidative stress and their associated damages.…”
Section: Phenolic Composition Of Limoniastrum Monopetalum Organssupporting
confidence: 93%
“…On the other hand, at the higher heating temperature (61°C), vanillin addition was still advantageous, but the microorganism inactivation was mostly due to thermal effect, as this temperature was closer to traditional pasteurization processes, rendering poorer sensory and nutritional quality. Delaquis et al (2005) determined the minimal inhibitory concentration (MIC) of vanillin for several species of Listeria in laboratory media at various pH levels. Reported L. monocytogenes and L. innocua MICs at pH 5.0 were 20 and 23 mM (3,000 and 3,500 ppm), respectively, suggesting that the former was slightly more sensitive.…”
Section: Combination Of Vanillin Citral and Mild Thermal Treatmentmentioning
confidence: 99%
“…The highest amount of vanillic acid in plants is found in the roots of Angelica sinensis [12]. Previous studies have shown the antifilarial [13], antibacterial [14], and antimicrobial [15] effects of vanillic acid. Vanillic acid also exhibits chemo preventive effect in experimentally induced carcinogenesis in rats [16].…”
Section: Introductionmentioning
confidence: 99%